BEM-ESTAR MATERNO E PROCESSOS DE INSERÇÃO ESCOLAR DE BEBÊS: UMA PROPOSTA DE SISTEMATIZAÇÃO - Silva, Viviane Ramos da (2017)
Admission of infants to school is the period of transition from care provided by the family system to care provided by the school system. It demands adaptation not only of the child, who is expected to interact with strangers in an unknown environment with new routines, but also of the family and the school because it requires reorganizations and transformations for all of them. The overall purpose of this study was to develop both a protocol, which aims to systematize the process of school admission of infants, and an explanatory folder as teaching tools. As specific objectives, the study aimed at the following: subsidizing the adherence of families to school as participants in the educational process; facilitating the admission process of infants from twelve to twenty-four months of age in a Centre for Early Childhood Education; verifying the relationship between maternal wellbeing and personality in the mothers’ and teachers’ perceptions regarding the adaption process of the infants to the school system; and analyzing the stability of two variables, which are “depressive symptoms” and “life satisfaction”. The study was based on a systematic literature review which focused on the relationships between the mothers' subjective wellbeing and the variations of child development. Furthermore, the link among life satisfaction, depressive symptoms and personality traits was analyzed through an empirical longitudinal study. It was developed between March and December of 2016 and investigated two educators and nine mothers of babies who joined a Centre for Early Childhood Education in the central region of the state of Rio Grande do Sul in the same year. Results found in previous studies have revealed the great influence of maternal wellbeing in the first years of a child’s life and the need to qualify the care provided to infants and young children in kindergartens and similar institutions. As a result, a protocol was organized to systematize the admission process of infants as well as an explanatory folder to be distributed in the Centre. Despite the extraordinary growth in Psychology studies on maternal health and child development, it has been found that the majority of them focus on the investigation of the symptoms and their effects, that is, they are based on the Traditional Psychology of a posteriori intervention. Therefore, this topic requires more studies of typical development, which aims at preventing misadjustments on behalf of children and their parents in order to increase subjective wellbeing, thus maximizing strengths and virtues of mothers or caregivers.